2006
DOI: 10.1038/sj.cdd.4401997
|View full text |Cite
|
Sign up to set email alerts
|

p66SHC promotes T cell apoptosis by inducing mitochondrial dysfunction and impaired Ca2+ homeostasis

Abstract: p66Shc, a redox enzyme that enhances reactive oxygen species (ROS) production by mitochondria, promotes T cell apoptosis. We have addressed the mechanisms regulating p66Shc-dependent apoptosis in T cells exposed to supraphysiological increases in [Ca 2 þ ] c . p66Shc expression resulted in profound mitochondrial dysfunction in response to the Ca 2 þ ionophore A23187, as revealed by dissipation of mitochondrial transmembrane potential, cytochrome c release and decreased ATP levels. p66Shc expression also caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 38 publications
(61 reference statements)
3
40
1
Order By: Relevance
“…In the intermembrane space, electron transfer between cytochrome c and activated p66Shc results in ROS generation that can initiate mitochondrial-induced apoptosis [35] (Figure 2). Although p66Shc-triggered ROS production is initiated by Ca 2+ and accompanied by alterations in mitochondrial Ca 2+ homeostasis [36], its effect on mitochondria does not necessarily depend on cytosolic Ca 2+ elevation [37]. In fact, deletion of the p66Shc longevity gene has been associated with reduced systemic and organ oxidative stress and a delay in the development of atherosclerosis in high-fat-fed mice [38], indicating the potential involvement of p66Shc in lipid-associated vascular disease and lipotoxicity.…”
Section: P66shc As a Link Between Cytosolic Protein Phosphorylation Amentioning
confidence: 99%
“…In the intermembrane space, electron transfer between cytochrome c and activated p66Shc results in ROS generation that can initiate mitochondrial-induced apoptosis [35] (Figure 2). Although p66Shc-triggered ROS production is initiated by Ca 2+ and accompanied by alterations in mitochondrial Ca 2+ homeostasis [36], its effect on mitochondria does not necessarily depend on cytosolic Ca 2+ elevation [37]. In fact, deletion of the p66Shc longevity gene has been associated with reduced systemic and organ oxidative stress and a delay in the development of atherosclerosis in high-fat-fed mice [38], indicating the potential involvement of p66Shc in lipid-associated vascular disease and lipotoxicity.…”
Section: P66shc As a Link Between Cytosolic Protein Phosphorylation Amentioning
confidence: 99%
“…19 Of these, the first involves dissipation of mitochondrial transmembrane potential and cytochrome c release due to an imbalance in the expression levels of proapoptotic/antiapoptotic Bcl-2 family members, 19 while the second involves Ca 2ϩ deregulation due to decreased expression and activity of plasma membrane Ca 2ϩ ATPases through the ROSelevating activity of p66Shc. 20 Submitted December 22, 2007; accepted March 7, 2008. Prepublished online as Blood First Edition paper, March 11, 2008; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%
“…19 Of these, the first involves dissipation of mitochondrial transmembrane potential and cytochrome c release due to an imbalance in the expression levels of proapoptotic/antiapoptotic Bcl-2 family members, 19 while the second involves Ca 2ϩ deregulation due to decreased expression and activity of plasma membrane Ca 2ϩ ATPases through the ROSelevating activity of p66Shc. 20 The defects found in p66Shc Ϫ/Ϫ T cells, as well as their enhanced proliferative responses to TCR agonists, suggest a potential impact of p66Shc deficiency in immune repertoire selection and lymphocyte homeostasis. Here we show that p66Shc Ϫ/Ϫ mice harbor spontaneous lymphocyte activation and develop a lupus-like autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…Opposite to the positive role exerted by p52Shc in Ag-receptor signaling, we recently showed that the 66-kDa isoform, which is expressed in lymphocytes and monocytes, albeit at lower levels compared with p52/p46Shc, inhibits TCR/BCR-dependent activation of the Ras-MAPK pathway and promotes T and B cell apoptosis (17,18). Furthermore, we demonstrated that ablation of the p66shc gene in mice leads to spontaneous lymphocyte activation and development of a lupus-like autoimmune disease, indicating a key role for p66Shc in controlling lymphocyte homeostasis (19).…”
mentioning
confidence: 99%